Solid electrolytic capacitors comprising a pre-coat and an intrinsically conductive polymer

By using intrinsic conductive polymers with specific structures in solid electrolytic capacitors, the problems of failure and instability of existing capacitors at high voltages are solved, and higher electrical performance stability and efficiency are achieved.

CN114787952BActive Publication Date: 2025-02-11KYOCERA AVX COMPONENTS CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080086154.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-12
Filing Date
2020-12-09
Publication Date
2025-02-11
Estimated Expiration
2040-12-09

AI Technical Summary

Technical Problem

Existing solid electrolytic capacitors fail at high voltages, have high leakage currents, and are unstable in electrical performance under certain conditions.

Method used

A solid electrolytic capacitor containing an intrinsic conductive polymer with a specific thiophene unit structure is used to improve the electrical properties of the capacitor by selectively controlling the characteristics of the precoat and solid electrolyte.

Benefits of technology

It achieves stable electrical performance under high voltage and high temperature conditions, reduces leakage current and equivalent series resistance, and improves capacitance stability and dielectric strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114787952B_ABST
    Figure CN114787952B_ABST
Patent Text Reader

Abstract

A solid electrolytic capacitor comprising a capacitor element is provided. The capacitor element comprises an anode body, a dielectric overlying the anode body, a pre-coating layer overlying the dielectric and formed of an organic metal compound, and a solid electrolyte overlying the dielectric. The solid electrolyte comprises an intrinsically conductive polymer comprising repeating thiophene units of a specific general formula.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to U.S. Provisional Application No. 62 / 945,912, filed on December 10, 2019, and U.S. Provisional Application No. 62 / 947,010, filed on December 12, 2019, the entire contents of which are incorporated herein by reference. Background Art

[0003] Solid electrolytic capacitors (e.g., tantalum capacitors) are typically made by pressing a metal powder (e.g., tantalum) around a metal lead, sintering the pressed component, anodizing the sintered anode, and thereafter applying a solid electrolyte. Conductive polymers are often used as solid electrolytes due to their advantageous low equivalent series resistance ("ESR") and "no burn / no ignition" failure mode. For example, such electrolytes can be formed by in situ chemical polymerization of 3,4-dioxythiophene monomer ("EDOT") in the presence of a catalyst and a dopant. However, conventional capacitors employing in situ polymerized polymers tend to have relatively high leakage currents ("DCL") and fail at high voltages, such as experienced during rapid turn-on or operating current spikes. To overcome these problems, dispersions formed from a composite of poly(3,4-ethylenedioxythiophene) (PEDOT) and poly(styrene sulfonic acid) (PSS) ("PEDOT:PSS") have also been used. Although PEDOT:PSS dispersions can improve leakage current values, other problems still exist. For example, one problem with polymer slurry-based capacitors is that they exhibit relatively poor electrical properties (e.g., capacitance stability) under certain conditions.

[0004] Therefore, there is a need for an improved solid electrolytic capacitor that exhibits relatively stable electrical performance. Summary of the invention

[0005] According to one embodiment of the present invention, a solid electrolytic capacitor is disclosed, which includes a capacitor element. The capacitor element includes an anode body, a dielectric covering the anode body, a pre-coating layer formed of an organic metal compound covering the dielectric, and a solid electrolyte covering the dielectric. The solid electrolyte includes an intrinsically conductive polymer, and the intrinsically conductive polymer includes repeating thiophene units of the following general formula (I):

[0006]

[0007] in,

[0008] a is 0 to 10;

[0009] b is 1 to 18;

[0010] R is an optionally substituted C1-C6 straight chain or branched alkyl group or a halogen atom; and

[0011] M is a hydrogen atom, an alkali metal, NH(R 1 )3, or HNC5H5, where R 1 Each is independently a hydrogen atom or an optionally substituted C1-C6 alkyl group.

[0012] Other features and aspects of the present invention will be described in more detail below. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In the remainder of this specification, a more particular description is given of a complete and enabling disclosure of the invention, including the best mode thereof, to one of ordinary skill in the art, with reference to the accompanying drawings, in which:

[0014] Figure 1 A cross-sectional view of one embodiment of a capacitor of the assembly of the present invention;

[0015] Figure 2 A cross-sectional view of another embodiment of a capacitor of the assembly of the present invention;

[0016] Figure 3 A cross-sectional view of yet another embodiment of a capacitor of the assembly of the present invention; and,

[0017] Figure 4 A top view of yet another embodiment of a capacitor that is an assembly of the present invention.

[0018] Repeat use of reference characters in the present specification and drawings is intended to represent the same or analogous features or elements of the invention. DETAILED DESCRIPTION

[0019] Those skilled in the art will appreciate that the present discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention, which are embodied in the exemplary constructions.

[0020] In general, the present invention relates to a solid electrolytic capacitor comprising a capacitor element including an anode body, a dielectric overlying the anode body, a pre-coating layer overlying the dielectric and formed of an organometallic compound, and a solid electrolyte overlying the dielectric. To help facilitate the use of the capacitor in high voltage applications, the solid electrolyte comprises an intrinsically conductive polymer comprising repeating thiophene units of the following general formula (I):

[0021]

[0022] in,

[0023] a is 0 to 10;

[0024] b is 1 to 18;

[0025] R is an optionally substituted C1-C6 straight chain or branched alkyl group or a halogen atom; and

[0026] M is a hydrogen atom, an alkali metal, NH(R 1 )3, or HNC5H5, where R 1 Each is independently a hydrogen atom or an optionally substituted C1-C6 alkyl group.

[0027] It is not intended to be limited by theory, it is believed that the specific properties of the selective control pre-coating and solid electrolyte in the above-mentioned manner can contribute to improve some electrical properties of the resulting capacitor.For example, the capacitor can present a relatively high "breakdown voltage" (voltage when the capacitor fails), such as about 55 volts or higher, about 65 volts or higher in some embodiments, about 85 volts or higher in some embodiments, about 90 volts or higher in some embodiments, about 95 volts or higher in some embodiments, and about 100 volts to about 300 volts in some embodiments, such as by increasing the applied voltage with an increment of 3 volts until the leakage current reaches 1mA to determine. The capacitor can present a high dielectric strength, which can improve capacitance stability." dielectric strength" generally refers to the ratio of the "breakdown voltage" (voltage when the capacitor fails, in volts, "V") of the capacitor to the dielectric thickness (in nanometers, "nm"). The capacitors typically exhibit a dielectric strength of about 0.4 V / nm or more, in some embodiments about 0.45 V / nm or more, in some embodiments about 0.5 V / nm or more, in some embodiments about 0.6 V / nm or more, in some embodiments about 0.65 V / nm or more, in some embodiments about 0.7 V / nm or more, in some embodiments about 0.75 V / nm to about 1 V / nm, and in some embodiments about 0.8 V / nm to about 0.9 V / nm. Although the dielectric thickness can generally vary depending on the particular location of the anode body, the "dielectric thickness" used to determine the dielectric strength is generally considered to be the maximum thickness of the dielectric, which is typically about 60 nm to about 500 nm, in some embodiments about 80 nm to about 350 nm, and in some embodiments about 100 nm to about 300 nm.

[0028] The resulting capacitor may be able to maintain stable electrical properties (e.g., capacitance) under a variety of different conditions. For example, the ratio of the capacitance ("charge-discharge capacitance") after being subjected to repeated cycles of a surge voltage (surge voltage) to the initial capacitance value before such testing can be about 0.7 to 1, in some embodiments about 0.8 to 1, in some embodiments 0.85 to 1, in some embodiments about 0.9 to 1, in some embodiments 0.91 to 0.99, and in some embodiments 0.92 to 0.99. The surge voltage may be applied for 1,000 to 16,000 cycles (e.g., 1,000, 2,000, 3,000, 4,000, 5,000, 8,000, 12,000, or 16,000 cycles). For example, after 5,000 cycles, the capacitor may exhibit a charge-discharge capacitance within the ranges mentioned above.

[0029] In addition, the capacitance can remain stable even after long exposure to high temperatures such as about 80°C or higher, in some embodiments, about 100°C to about 150°C, in some embodiments, about 105°C to about 130°C (e.g., 105°C or 125°C), such as about 100 hours or longer, and in some embodiments, about 150 hours to about 3,000 hours (e.g., 3,000 hours). In one embodiment, for example, the ratio of the capacitance after exposure to high temperature (e.g., 105°C) for 3,000 hours to the initial capacitance value (e.g., 23°C) is about 0.7 to 1, in some embodiments, about 0.8 to 1, in some embodiments, about 0.9 to 1, and in some embodiments, about 0.91 to 0.99. The actual capacitance value (dry) may vary, but the actual capacitance value measured at a frequency of 120 Hz is typically about 1 millifarad / square centimeter ("mF / cm 2 ”) or more, in some embodiments about 2 mF / cm 2 or more, in some embodiments about 5 mF / cm 2 To about 50mF / cm 2 , and in some embodiments, about 8 mF / cm 2 To about 20mF / cm 2 .

[0030] In addition to those mentioned above, the capacitor can also exhibit other improved electrical properties. For example, after being subjected to an applied voltage (e.g., 120 volts) for a period of time, the capacitor can exhibit a leakage current ("DCL") of only about 100 microamperes ("μA") or less, in some embodiments about 70μA or less, and in some embodiments about 1μA to about 50μA, the period of time being about 30 minutes to about 20 hours, in some embodiments about 1 hour to about 18 hours, and in some embodiments about 4 hours to about 16 hours. It is worth noting that even under dry conditions such as those described above, the capacitor can also exhibit such low DCL values. The capacitor can also exhibit a relatively low equivalent series resistance (equivalence series resistance, "ESR"), such as an equivalent series resistance measured at an operating frequency of 100kHz and a temperature of 23°C of about 200mohms, less than about 150mohms in some embodiments, about 0.1mohms to about 125mohms in some embodiments, and about 1mohms to about 100mohms in some embodiments. The capacitor can exhibit such an ESR value even after long-term exposure to a temperature of about 80°C or higher, in some embodiments, about 100°C to about 150°C, in some embodiments, about 105°C to about 130°C (e.g., 105°C or 125°C), such as about 100 hours or more, and in some embodiments, about 150 hours to about 3,000 hours (e.g., 3,000 hours). In one embodiment, for example, the ratio of the ESR of the capacitor after exposure to high temperature (e.g., 105°C) for 3,000 hours to the initial ESR value of the capacitor (e.g., at 23°C) is about 2.0 or less, in some embodiments, about 1.5 or less, and in some embodiments, about 1.0 to about 1.3.

[0031] It is also believed that the dissipation factor of the capacitor can be maintained at a relatively low level. The dissipation factor generally refers to the losses that occur in a capacitor and is generally expressed as a percentage of the ideal capacitor performance. For example, the dissipation factor of a capacitor measured at a frequency of 120 Hz is typically about 250% or less, in some embodiments about 200% or less, and in some embodiments about 1% to about 180%.

[0032] Various embodiments of the capacitor will now be described in more detail.

[0033] I. Capacitor Components

[0034] A. Anode

[0035] The capacitor element includes an anode comprising a dielectric formed on an anode body. The anode body can be in the form of a sheet, foil, mesh, pellet, etc. Regardless of the form of the anode body, the anode body is typically formed of a valve metal (i.e., a metal that can be oxidized) or a valve metal compound (such as tantalum, niobium, aluminum, hafnium, titanium, their alloys, their oxides, their nitrides, etc.). For example, in one embodiment, the anode body can be in the form of a foil comprising aluminum. In another embodiment, the anode body can be in the form of a pellet comprising tantalum, niobium, or their oxides. For example, tantalum powder can be formed by a reduction process in which a tantalum salt (e.g., potassium fluorotantalate (K2TaF7), sodium fluorotantalate (Na2TaF7), tantalum pentachloride (TaCl5), etc.) reacts with a reducing agent. The reducing agent can be provided in the form of a liquid, a gas (e.g., hydrogen), or a solid (such as a metal (e.g., sodium), a metal alloy, or a metal salt). For example, in one embodiment, a tantalum salt (e.g., TaCl5) may be heated at a temperature of about 900°C to about 2,000°C, in some embodiments, about 1,000°C to about 1,800°C, and in some embodiments, about 1,100°C to about 1,600°C to form a vapor that can be reduced in the presence of a gaseous reducing agent (e.g., hydrogen). Additional details of such a reduction reaction may be described in Maeshima et al. After reduction, the product can be cooled, crushed and washed to form a powder.

[0036] When employed, the specific charge of the powder typically varies from about 2,000 microfarads*volts / gram to about 600,000 microfarads*volts / gram ("μF*V / g"), depending on the desired application. For example, in certain embodiments, a high charge powder having a specific charge of about 100,000 μF*V / g to about 600,000 μF*V / g, in some embodiments, about 120,000 μF*V / g to about 500,000 μF*V / g, and in some embodiments, about 150,000 μF*V / g to about 400,000 μF*V / g may be employed. In other embodiments, a low charge powder may be employed having a specific charge of about 2,000 μF*V / g to about 100,000 μF*V / g, in some embodiments about 5,000 μF*V / g to about 80,000 μF*V / g, and in some embodiments about 10,000 μF*V / g to about 70,000 μF*V / g. As is known in the art, the specific charge can be determined by multiplying the capacitance by the anodizing voltage employed and then dividing the product by the weight of the anodized electrode body. The powder may be a free-flowing finely divided powder containing primary particles. The median size (D50) of the primary particles of the powder is generally about 5 nanometers to about 500 nanometers, about 10 nanometers to about 400 nanometers, and about 20 nanometers to about 250 nanometers in some embodiments, such as, optionally, after subjecting the particles to 70 seconds of ultrasonic vibration, using a laser particle size distribution analyzer (e.g., LS-230) manufactured by Beckman Coulter Corporation. The primary particles typically have a three-dimensional particle shape (e.g., nodular or angular). Such particles typically have a relatively low "aspect ratio", which is the average diameter or width of the particles divided by the average thickness ("D / T"). For example, the aspect ratio of the particles can be about 4 or lower, about 3 or lower in some embodiments, and about 1 to about 2 in some embodiments. In addition to primary particles, the powder can also contain other types of particles, such as secondary particles formed by aggregating (or agglomerating) primary particles. Such secondary particles may have a median size (D50) of from about 1 micron to about 500 microns, and in some embodiments, from about 10 microns to about 250 microns.

[0037] Agglomeration of the particles can occur by heating the particles and / or by using a binder. For example, agglomeration can occur at a temperature of about 0°C to about 40°C, in some embodiments about 5°C to about 35°C, and in some embodiments about 15°C to about 30°C. Suitable binders may likewise include, for example, poly(vinyl butyral); poly(vinyl acetate); poly(vinyl alcohol); poly(vinyl pyrrolidone); cellulosic polymers such as carboxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose and methyl hydroxyethyl cellulose; random polypropylene, polyethylene; polyethylene glycol (e.g., Carbowax from Dow Chemical Co.); polystyrene, poly(butadiene / styrene); polyamides, polyimides and polyacrylamides, high molecular weight polyethers; copolymers of ethylene oxide and propylene oxide; fluoropolymers such as polytetrafluoroethylene, polyvinylidene fluoride, and fluoroolefin copolymers; acrylic polymers such as sodium polyacrylate, poly(lower alkyl acrylates), poly(lower alkyl methacrylates), and copolymers of lower alkyl acrylates and methacrylates; and fatty acids and waxes such as stearic acid and other soapy fatty acids, vegetable waxes, microcrystalline waxes (purified paraffin waxes), and the like.

[0038] The resulting powder can be compacted to form pellets using any conventional powder compacting equipment. For example, a press die can be used, which is a single station compaction press containing a die and one or more punches. Alternatively, an anvil type compaction press using only a die and a single lower punch can be used. Single station compaction presses can be used in several basic types, such as cam presses, toggle / elbow presses, and eccentric / crank presses with multiple functions (such as single action, double action, floating die, movable platen, opposed ram, screw, impact, hot pressing, coining or sizing). The powder can be compacted around an anode lead, which can be in the form of a wire, sheet, etc. The lead can extend from the anode body in a longitudinal direction and can be formed of any conductive material (such as tantalum, niobium, aluminum, hafnium, titanium, etc., and their conductive oxides and / or nitrides). Connection of the lead to the anode body may also be accomplished using other known techniques, such as by welding the lead to the anode body, or embedding the lead within the anode body during the formation process (eg, prior to compaction and / or sintering).

[0039] After pressing, any binder can be removed by heating the pellets under vacuum at a temperature (e.g., about 150° C. to about 500° C.) for several minutes. Alternatively, the binder can also be removed by contacting the pellets with an aqueous solution, such as Bishop et al. Described in U.S. Patent No. 6,197,252. Afterwards, the pellets are sintered to form a porous integral mass. The pellets are typically sintered at a temperature of about 700°C to about 1800°C, about 800°C to about 1700°C in some embodiments, and about 900°C to about 1400°C for about 5 minutes to about 100 minutes, and about 8 minutes to about 15 minutes in some embodiments. This can occur in one or more steps. If necessary, sintering can occur in an atmosphere that limits the transfer of oxygen atoms to the anode. For example, sintering can occur in a reducing atmosphere (such as vacuum, inert gas, hydrogen, etc.). The pressure of the reducing atmosphere can be about 10 torr to about 2000 torr, about 100 torr to about 1000 torr in some embodiments, and about 100 torr to about 930 torr in some embodiments. A mixture of hydrogen and other gases (e.g., argon or nitrogen) can also be used.

[0040] B. Dielectric

[0041] The anode is also coated with a dielectric. As described above, the dielectric is formed by anodizing ("anodizing") the anode so that a dielectric layer is formed over and / or within the anode. For example, a tantalum (Ta) anode may be anodized to tantalum pentoxide (Ta2O5), while an aluminum (Al) anode may be anodized to aluminum pentoxide (Al2O5).

[0042] Typically, anodization is performed by initially applying an electrolyte to the anode, such as by immersing the anode in the electrolyte. The electrolyte is generally in liquid form, such as a solution (e.g., aqueous or non-aqueous), a dispersion, a melt, etc. Solvents are generally used in the electrolyte, such as water (e.g., deionized water); ethers (e.g., diethyl ether and tetrahydrofuran); glycols (e.g., ethylene glycol, propylene glycol, etc.); alcohols (e.g., methanol, ethanol, n-propanol, isopropanol, and butanol); triglycerides; ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate, and methoxypropyl acetate); amides (e.g., dimethylformamide, dimethylacetamide, dimethyloctanoic acid / decanoic acid amide, and N-alkylpyrrolidone); nitriles (e.g., acetonitrile, propionitrile, butyronitrile, and benzonitrile); and sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and sulfolane); etc. The solvent can constitute about 50wt.% to about 99.9wt.% of the electrolyte, about 75wt.% to about 99wt.% in some embodiments, and about 80wt.% to about 95wt.% in some embodiments. Although not required, it is often desirable to use an aqueous solvent (e.g., water) to promote the formation of oxides. In fact, water can constitute about 1wt.% or more of the solvent used in the electrolyte, about 10wt.% or more in some embodiments, about 50wt.% or more in some embodiments, about 70wt.% or more in some embodiments, and about 90wt.% to 100wt.% in some embodiments.

[0043] The electrolyte is electrically conductive and may have an electrical conductivity of about 1 millisiemens / cm ("mS / cm") or greater, in some embodiments about 30 mS / cm or greater, and in some embodiments about 40 mS / cm to about 100 mS / cm, measured at a temperature of 25°C. To increase the conductivity of the electrolyte, an ionic compound that is capable of dissociating in a solvent to form ions is typically used. Suitable ionic compounds for this purpose may include, for example, acids such as nitric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, boric acid, boric acid, acid) and the like; organic acids, including carboxylic acids and sulfonic acids, such as acrylic acid, methacrylic acid, malonic acid, succinic acid, salicylic acid, sulfosalicylic acid, adipic acid, maleic acid, malic acid, oleic acid, gallic acid, tartaric acid, citric acid, formic acid, acetic acid, glycolic acid, oxalic acid, propionic acid, phthalic acid, isophthalic acid, glutaric acid, gluconic acid, lactic acid, aspartic acid, glutamic acid, itaconic acid, trifluoroacetic acid, barbituric acid, cinnamic acid, benzoic acid, 4-hydroxybenzoic acid, aminobenzoic acid and the like; sulfonic acids such as methanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, trifluoromethanesulfonic acid, styrenesulfonic acid, naphthalene disulfonic acid, hydroxybenzenesulfonic acid, dodecylsulfonic acid, dodecylbenzenesulfonic acid and the like; polymeric acids, such as poly(acrylic acid) or poly(methacrylic acid) and copolymers thereof (e.g., maleic acid-acrylic acid copolymer, sulfonic acid-acrylic acid copolymer and styrene-acrylic acid copolymer), carrageenic acid (carageenic acid) and sulfonic acid. acid), carboxymethyl cellulose, alginic acid, etc.; and so on. The concentration of the ionic compound is selected to achieve the desired conductivity. For example, the acid (e.g., phosphoric acid) can constitute about 0.01 wt.% to about 5 wt.% of the electrolyte, in some embodiments, about 0.05 wt.% to about 0.8 wt.%, and in some embodiments, about 0.1 wt.% to about 0.5 wt.%. If desired, a blend of ionic compounds can also be used in the electrolyte.

[0044] In order to form the dielectric, typically, an electric current is passed through the electrolyte while the electrolyte is in contact with the anode body. The value of the formation voltage controls the thickness of the dielectric layer. For example, the power supply can be initially set to a constant current mode until the desired voltage is reached. Afterwards, the power supply can be switched to a constant potential mode to ensure that the desired dielectric thickness is formed over the entire surface of the anode. Of course, other known methods, such as a pulsed constant potential method or a step-by-step constant potential method, can also be used. The voltage range at which anodization occurs is typically about 4V to about 250V, about 5V to about 200V in some embodiments, and about 10V to about 150V in some embodiments. During oxidation, the electrolyte can be kept at an elevated temperature, such as about 30°C or higher, about 40°C to about 200°C in some embodiments, and about 50°C to about 100°C in some embodiments. Anodization can also be performed at ambient temperature or a lower temperature. The resulting dielectric layer can be formed on the surface of the anode and in the pores of the anode.

[0045] Although not necessary, in certain embodiments, the dielectric layer can have different thicknesses over the entire anode, because the dielectric layer has a first portion covering the outer surface of the anode and a second portion covering the inner surface of the anode. In such an embodiment, the first portion is selectively formed so that the thickness of the first portion is greater than the thickness of the second portion. However, it should be understood that the thickness of the dielectric layer in a specific area does not need to be uniform. For example, some parts of the dielectric layer adjacent to the outer surface can actually be thinner than some parts of the layer at the inner surface, and vice versa. Nevertheless, the dielectric layer can be formed so that at least a portion of the layer at the outer surface has a greater thickness than at least a portion at the inner surface. Although the exact difference in these thicknesses can vary according to specific applications, the ratio of the thickness of the first portion to the thickness of the second portion is typically about 1.2 to about 40, about 1.5 to about 25 in some embodiments, and about 2 to about 20 in some embodiments.

[0046] In order to form a dielectric layer with different thicknesses, a multi-stage process can be used. In each stage of the process, the sintered anode is anodized ("anodized") to form a dielectric layer (e.g., tantalum pentoxide). During the first stage of anodization, a relatively small formation voltage is typically used to ensure that the desired dielectric thickness for the internal region is achieved, such as, the formation voltage ranges from about 1 volt to about 90 volts, in some embodiments about 2 volts to about 50 volts, and in some embodiments about 5 volts to about 20 volts. Afterwards, the sintered body can be anodized in the second stage of the process to increase the thickness of the dielectric to a desired level. This is usually achieved by anodizing in an electrolyte at a voltage higher than the voltage used during the first stage, such as, the formation voltage ranges from about 50 volts to about 350 volts, in some embodiments about 60 volts to about 300 volts, and in some embodiments about 70 volts to about 200 volts. During the first stage and / or the second stage, the electrolyte may be maintained at a temperature ranging from about 15°C to about 95°C, in some embodiments, from about 20°C to about 90°C, and in some embodiments, from about 25°C to about 85°C.

[0047] The electrolyte used during the first and second stages of the anodizing process may be the same or different. However, typically, the electrolyte used in at least one stage of the dielectric development process contains an ionic compound as described above. In a particular embodiment, it may be desirable that the electrolyte used in the second stage has a lower ionic conductivity than the electrolyte used in the first stage to prevent the formation of a large amount of oxide film on the inner surface of the anode. In this regard, the electrolyte used during the first stage may contain an ionic compound, which is an acid, such as hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, polyphosphoric acid, boric acid, boric acid, etc. Such an electrolyte may have a conductivity of about 0.1mS / cm to about 100mS / cm, about 0.2mS / cm to about 20mS / cm, and about 1mS / cm to about 10mS / cm measured at a temperature of 25°C. The electrolyte used during the second stage may also contain an ionic compound, which is a salt of a weak acid, so that the concentration of hydronium ions in the pores increases due to the charge channel therein. Ion transport or diffusion makes weak acid anions move to the pores as required to balance charge.As a result, in the balance between hydronium ions, acid anions and undissociated acid, the concentration of the main conductive material (hydronium ions) is reduced, so that a poorly conductive material is formed.The reduction in the concentration of conductive materials causes a relatively high voltage drop in the electrolyte, which hinders further anodization of the interior, and sets up a thicker oxide layer on the exterior, to reach a higher formation voltage in the region of continuous high conductivity.Suitable weak acid salts can, for example, include ammonium salts or alkali metal salts (for example, sodium, potassium, etc.) of boric acid, boric acid, acetic acid, oxalic acid, lactic acid, adipic acid, etc. Particularly suitable salts include sodium tetraborate and ammonium pentaborate.Such electrolytes typically have a conductivity of about 0.1mS / cm to about 20mS / cm, about 0.5mS / cm to about 10mS / cm, and about 1mS / cm to about 5mS / cm measured at a temperature of 25°C, in some embodiments.

[0048] If necessary, each stage of anodization can be repeated for one or more cycles to obtain the desired dielectric thickness. In addition, after the first stage and / or the second stage, the anode can also be cleaned or washed with another solvent (e.g., water) to remove the electrolyte.

[0049] C. Pre-coating

[0050] A pre-coating layer may be used overlying the dielectric, the pre-coating layer being located between the dielectric and the solid electrolyte. The pre-coating layer typically comprises an organometallic compound, such as a compound having the following general formula (II):

[0051]

[0052] in,

[0053] Z is an organic metal atom, such as silicon, titanium, etc.;

[0054] R1, R2 and R3 are independently alkyl (e.g., methyl, ethyl, propyl, etc.) or hydroxyalkyl (e.g., hydroxymethyl, hydroxyethyl, hydroxypropyl, etc.), wherein at least one of R1, R2 and R3 is hydroxyalkyl;

[0055] n is an integer from 0 to 8, in some embodiments an integer from 1 to 6, and in some embodiments an integer from 2 to 4 (e.g., 3); and,

[0056] X is an organic or inorganic functional group, such as glycidyl, glycidyloxy, mercapto, amino, vinyl, and the like.

[0057] In certain embodiments, at least one of R1, R2 and R3 in formula (II) can be a hydroxyalkyl group (e.g., OCH3). For example, each of R1, R2 and R3 can be a hydroxyalkyl group. However, in other embodiments, R1 can be an alkyl group (e.g., CH3), and R2 and R3 can be a hydroxyalkyl group (e.g., OCH3).

[0058] In certain embodiments, X can be an amino group. Suitable amino-functional organosilane compounds can include, for example, monoamino-functional silanes having the following general formula (II):

[0059]

[0060] in,

[0061] R1, R2 and R3 are as defined above;

[0062] R4 and R5 are independently hydrogen, alkyl, independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl, hydroxyalkyl, or optionally N, and R4 and R5 together with one or more additional atoms form a ring structure (e.g., heteroaryl or heterocyclyl); and

[0063] Z is an organic group linking the nitrogen atom and the silicon atom, such as an alkyl group (eg, ethyl or propyl), an aryl group (eg, phenyl), or the like.

[0064] Examples of monoamino-functionalized silane compounds may include, for example, primary amine compounds (e.g., 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, aminophenyltrimethoxysilane, 3-aminopropyltri(methoxy-ethoxy)silane, 11-aminoundecyltriethoxysilane, 2(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, N-(3-trimethoxysilylpropyl)pyrrole, 3-(m-aminophenoxy)propyltrimethoxysilane, aminopropyltrihydroxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, etc. ); secondary amine compounds (e.g., N-butylaminopropyl trimethoxysilane, N-ethylaminoisobutyltrimethoxysilane, N-methylaminopropyl trimethoxysilane, N-phenylaminopropyl trimethoxysilane, 3-(N-allylamino)propyl trimethoxysilane, cyclohexylaminomethyl triethoxysilane, N-cyclohexylaminopropyl trimethoxysilane, N-ethylaminoisobutylmethyldiethoxysilane, (phenylaminoethyl)methyl-diethoxysilane, N-phenylaminomethyl trimethoxysilane, N-methylaminopropylmethyl-dimethoxysilane, etc.); tertiary amine compounds (e.g., bis(2-hydroxyethyl)3-aminopropyl triethoxysilane, diethylaminomethyl triethoxysilane, (N,N-diethyl-3-aminopropyl) trimethoxysilane, etc.); and combinations thereof. In addition, if desired, an additional group may be bonded to the nitrogen atom so that the compound is a quaternary amine functionalized silane compound.

[0065] Diamino-functional silane compounds may also be used, such as those having the following general formula (III):

[0066]

[0067] in,

[0068] R1, R2, R 3、 R4 and R5 are as defined above;

[0069] Z1 is an organic group connecting the nitrogen atom to the silicon atom, and Z2 is an organic group connecting the nitrogen atom, such as an alkyl group (e.g., ethyl or propyl group), an aryl group (e.g., phenyl group), etc. Examples of such diamino-functionalized silane compounds may include, for example, N-(2-aminoethyl)-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(6-aminohexyl)aminomethyltriethoxysilane, N-(6-aminohexyl)amino-propyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, (aminoethylaminomethyl)-phenethyltrimethoxysilane, N-3-[ (Amino(polypropyleneoxy)]-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrihydroxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylamino)-3-isobutyldimethylmethoxysilane, or a combination thereof. Triamino non-functional compounds such as (3-trimethoxysilylpropyl)-diethylenetriamine may also be used.

[0070] Of course, as described above, other functional groups may also be used. For example, sulfur-functionalized silane compounds such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 2,2-dimethoxy-1-thia-2-silacyclopentane, 11-mercaptoundecyltrimethoxysilane, S-(octanoyl)mercaptopropyltriethoxysilane, 2-(2-pyridylethyl)thiopropyl-trimethoxysilane, 2-(4 ... 2-(3-trimethoxysilylpropylthio)-thiophene, mercaptomethylmethyldiethoxysilane, 3-mercaptopropylmethyldimethoxysilane, bis[3-(triethoxysilyl)propyl]tetrasulfide, bis[3-(triethoxysilyl)propyl]disulfide, bis[m-(2-triethoxysilylethyl)tolyl]polysulfide, bis[3-(triethoxysilyl)propyl]thiourea, and the like, and combinations thereof.

[0071] The specific mode of applying the precoat layer to the capacitor body can be changed as needed. In a specific embodiment, the compound is dissolved in an organic solvent and applied to the parts as a solution, such as by screen printing, immersion, electrophoretic coating, spraying, etc. The organic solvent can vary, but typically alcohols, such as methanol, ethanol, etc. The organometallic compound can constitute about 0.1wt.% to about 10wt.% of the solution, about 0.2wt.% to about 8wt.% in some embodiments, and about 0.5wt.% to about 5wt.% in some embodiments. The solvent can also constitute about 90wt.% to about 99.9wt.% of the solution, about 92wt.% to about 99.8wt.% in some embodiments, and about 95wt.% to about 99.5wt.% in some embodiments. Once applied, the parts can then be dried to remove the solvent therefrom and form a precoat layer containing the organometallic compound.

[0072] D. Solid Electrolyte

[0073] The solid electrolyte overlies the pre-coating layer and generally functions as a cathode for the capacitor. Typically, the total thickness of the solid electrolyte is from about 1 μm to about 50 μm, in some embodiments from about 5 μm to about 20 μm. As described above, the solid electrolyte includes an intrinsically conductive polymer comprising repeating thiophene units having the following general formula (I):

[0074]

[0075] in,

[0076] a is 0 to 10, in some embodiments 0 to 6, and in some embodiments 1 to 4 (e.g., 1);

[0077] b is 1 to 18, in some embodiments 1 to 10, and in some embodiments 2 to 6 (e.g., 2, 3, 4, or 5);

[0078] R is an optionally substituted C1-C6 straight chain or branched alkyl (methyl) group or a halogen atom (eg, fluorine);

[0079] M is a hydrogen atom, an alkali metal (e.g., Li, Na, or K), NH(R 1 )3, or HNC5H5, where R 1 Each is independently a hydrogen atom or an optionally substituted C1-C6 alkyl group.

[0080] Specific examples for forming such repeating thiophene compounds are described in U.S. Pat. No. 9,718,905 and may include, for example, sodium 3-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1-propanesulfonate, Sodium propane sulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propane sulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propane sulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propane sulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propane sulfonate Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate ]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid potassium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid ammonium, 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid triethylamine or a combination thereof. Each of the above-exemplified thiophene monomers can be prepared from thieno[3,4-b]-1,4-dioxin-2-methanol and a branched sultone compound according to a known method (for example, Journal of Electroanalytical Chemistry, 443, 217 to 226 (1998)).

[0081] Intrinsically conductive polymers can be formed by various techniques that will be understood by those skilled in the art. In a particular embodiment, for example, a thiophene compound having the general formula (I) can be polymerized in the presence of an oxidation catalyst. Derivatives of these monomers, such as dimers or trimers of the above compounds, can also be used. The derivatives can be composed of the same or different monomer units and used in pure form, as well as in the form of a mixture with each other and / or with monomers. Oxidized or reduced forms of these precursors can also be used. The amount of the oxidation catalyst used in the polymerization reaction is not particularly limited, and the amount of the oxidation catalyst can be 1 to 50 molar times, more preferably 1 to 20 molar times, relative to the molar number of the thiophene compound used as a charged material. The oxidation catalyst can be a transition metal salt, such as a salt of an inorganic or organic acid containing ammonium, sodium, gold, iron (III), copper (II), chromium (VI), cerium (IV), manganese (IV), manganese (VII) or ruthenium (III) cations. Particularly suitable transition metal salts include halides (e.g., FeCl3 or HAuCl4); salts of other inorganic acids (e.g., Fe(ClO4)3, Fe2(SO4)3, (NH4)2S2O8, or Na3Mo 12 PO 40 ); and salts of organic acids and inorganic acids containing organic groups. Examples of inorganic acid salts having organic groups include, for example, C1 to C 20 iron (III) salts of sulfuric acid monoesters of alkanols (e.g., iron (III) salts of dodecyl sulfate). Similarly, examples of salts of organic acids include, for example, C1 to C 20 an iron(III) salt of an alkanesulfonic acid (e.g., methanesulfonic acid, ethanesulfonic acid, propanesulfonic acid, butanesulfonic acid, or dodecanesulfonic acid); an iron(III) salt of an aliphatic perfluorosulfonic acid (e.g., trifluoromethanesulfonic acid, perfluorobutanesulfonic acid, or perfluorooctanesulfonic acid); an aliphatic C1 to C 20 carboxylic acid (e.g., 2-ethylhexyl carboxylic acid); an iron (III) salt of an aliphatic perfluorocarboxylic acid (e.g., trifluoroacetic acid or perfluorooctanoic acid); optionally C1 to C 20 Iron (III) salts of alkyl-substituted aromatic sulfonic acids (e.g., benzenesulfonic acid, o-toluenesulfonic acid, p-toluenesulfonic acid, or dodecylbenzenesulfonic acid); iron (III) salts of cycloalkanesulfonic acids (e.g., camphorsulfonic acid); etc. Mixtures of these above salts may also be used.

[0082] Oxidative polymerization usually occurs in the presence of one or more solvents. Suitable solvents may include, for example, water, glycols (e.g., ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiethylene glycol, dipropylene glycol, etc.); glycol ethers (e.g., methyl glycol ether, ethyl glycol ether, isopropyl glycol ether, etc.); alcohols (e.g., methanol, ethanol, n-propanol, isopropanol, and butanol); ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone); esters (e.g., ethyl acetate, butyl acetate, glycol ether acetate, methoxypropyl acetate, ethylene carbonate, propylene carbonate, etc.); amides (e.g., dimethylformamide, dimethylacetamide, dimethyloctanoic acid / decanoic acid amide, and N-alkylpyrrolidone); sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and sulfolane); phenolic compounds (e.g., toluene, xylene, etc.), etc. Water is a particularly suitable solvent for the reaction. The amount of solvent used in the polymerization reaction is not particularly limited as long as the thiophene compound used as a raw material is dissolved in the solvent, but is preferably 0.1 to 100 times, more preferably 0.1 to 50 times the weight of the added thiophene compound. The temperature at which the reaction takes place typically varies between about -20°C and about 140°C, and in some embodiments, between about 20°C and about 100°C. After the reaction is completed, any salt impurities can be removed using known purification techniques, such as by washing with a solvent, reprecipitation, centrifugal sedimentation, ultrafiltration, dialysis or ion exchange resin treatment, and combinations thereof.

[0083] Regardless of how it is formed, as long as there is a positive charge on the polymer located on the main chain, at least partially compensated by anions covalently bound to the polymer, the polymer is considered to be "intrinsically" conductive. For example, the relatively high specific conductivity of the polymer in the dry state can be about 1 Siemens per centimeter ("S / cm") or more, in some embodiments about 10S / cm or more, in some embodiments about 25S / cm or more, in some embodiments about 40S / cm or more, and in some embodiments about 50S / cm to about 500S / cm. Due to its intrinsic conductivity, the solid electrolyte does not require the addition of traditional dopants, such as polystyrene sulfonic acid. In fact, the solid electrolyte can be substantially free of such dopants. However, it should be understood that dopants can be used in certain embodiments of the present invention. However, when used, the dopant is generally present in the solid electrolyte in an amount of about 5wt.% or less, in some embodiments about 2wt.% or less, and in some embodiments about 1wt.% or less.

[0084] The polymer is also typically highly soluble in water, which enables it to be applied to the anode more easily and efficiently. The soluble polymer can also more easily impregnate the small pores formed by the high specific charge powder, so that the resulting solid electrolyte has a "film-like" configuration and covers at least a portion of the anode in a substantially uniform manner. This improves the quality of the resulting oxide and its surface coverage, thereby improving the electrical performance of the capacitor assembly.

[0085] i. Inner layer

[0086] Solid electrolytes are usually formed by one or more "inner" conductive polymer layers. In this article, the term "inner" refers to one or more layers formed by the same material, and the one or more layers are directly or via another layer overlying the pre-coating layer. For example, the inner layer typically comprises an intrinsic conductive polymer as described above. In a specific embodiment, the inner layer is usually free of non-intrinsically conductive polymers (extrinsically conductive polymers), and is therefore mainly formed by conductive polymers. More specifically, the intrinsic conductive polymer can constitute about 50wt.% or more of the inner layer, about 70wt.% or more in some embodiments, and about 90wt.% or more (e.g., 100wt.%). One or more inner layers can be used. For example, the solid electrolyte typically contains 2 to 30, 4 to 20 in some embodiments, and about 5 to 15 (e.g., 10) inner layers in some embodiments.

[0087] The inner layer can be applied in the form of a solution containing a solvent. The concentration of the polymer can vary according to the desired viscosity and the specific mode in which the layer is applied to the anode. However, typically, the polymer constitutes about 0.1wt.% to about 10wt.% of the solution, about 0.4wt.% to about 5wt.% in some embodiments, and about 0.5wt.% to about 4wt.% in some embodiments. Similarly, the solvent can constitute about 90wt.% to about 99.9wt.% of the solution, about 95wt.% to about 99.6wt.% in some embodiments, and about 96wt.% to about 99.5wt.% in some embodiments. Although other solvents can certainly be used, it is generally desired that water is the main solvent so that the solution is considered to be an "aqueous" solution. In most embodiments, for example, water constitutes at least about 50wt.% of the solvent used, at least about 75wt.% in some embodiments, and about 90wt.% to 100wt.% in some embodiments. When a solution is used, the solution can be applied to the anode using any known technique, such as dipping, casting (e.g., curtain coating, spin coating, etc.), printing (e.g., gravure printing, offset printing, screen printing, etc.), etc. After the resulting conductive polymer layer is applied to the anode, the conductive polymer can be dried and / or washed.

[0088] ii. Outer layer

[0089] The solid electrolyte may comprise only an "inner layer" so that the solid electrolyte is substantially formed by the same material (i.e., an intrinsic conductive polymer). Nevertheless, in other embodiments, the solid electrolyte may also contain one or more optional "outer" conductive polymer layers, which are formed by a material different from the inner layer and are coated on the inner layer. For example, the outer layer may be formed by a non-intrinsic conductive polymer. In a particular embodiment, the outer layer is mainly formed by such a non-intrinsic conductive polymer, wherein they constitute about 50wt.% or more of the corresponding outer layer, about 70wt.% or more in some embodiments, and about 90wt.% or more (e.g., 100wt.%). One or more outer layers may be used. For example, the solid electrolyte may contain 2 to 30, 4 to 20 in some embodiments, and about 5 to 15 outer layers in some embodiments.

[0090] When used, the extrinsic conductive polymer may, for example, have a repeating unit of the following formula (IV):

[0091]

[0092] in,

[0093] R7 is: a linear or branched C1 to C18 Alkyl groups (e.g., methyl, ethyl, n-propyl or isopropyl, n-butyl, isobutyl, sec-butyl or tert-butyl, n-pentyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1,1-dimethylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, n-hexadecyl, n-octadecyl, etc.); C5 to C 12 Cycloalkyl groups (e.g., cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, cyclodecyl, etc.); C6 to C 14 Aryl group (e.g., phenyl, naphthalene, etc.); C7 to C 18 an aralkyl group (e.g., benzyl, o-tolyl, m-tolyl, p-tolyl, 2,3-xylyl, 2,4-xylyl, 2,5-xylyl, 2-6-xylyl, 3-4-xylyl, 3,5-xylyl, mesityl, etc.); a C1 to C4 hydroxyalkyl group or a hydroxyl group; and

[0094] q is an integer from 0 to 8, in some embodiments from 0 to 2, and in one embodiment is 0. In a specific embodiment, "q" is 0 and the polymer is poly(3,4-ethylenedioxythiophene). A commercially suitable example of a monomer suitable for forming such a polymer is 3,4-ethylenedioxythiophene, which is available from Heraeus under the trade name Clevios TM M obtained.

[0095] To the extent that polymers of formula (IV) generally require the presence of a separate counterion that is not covalently bound to the polymer, polymers of formula (IV) are generally considered to be "non-intrinsically" conductive. The counterion can be a monomeric anion or a polymeric anion that counteracts the charge of the conductive polymer. The polymeric anion can be, for example, an anion of a polymeric carboxylic acid (e.g., polyacrylic acid, polymethacrylic acid, polymaleic acid, etc.); a polymeric sulfonic acid (e.g., polystyrene sulfonic acid ("polystyrene sulfonic acid, PSS"), polyvinyl sulfonic acid, etc.); and the like. The acid can also be a copolymer, such as a copolymer of vinyl carboxylic acid and vinyl sulfonic acid, and other polymerizable monomers (such as acrylates and styrene). Similarly, suitable monomeric anions include, for example, anions of: C1 to C 20 Alkane sulfonic acid (e.g., dodecane sulfonic acid); aliphatic perfluorosulfonic acid (e.g., trifluoromethane sulfonic acid, perfluorobutane sulfonic acid, or perfluorooctane sulfonic acid); aliphatic C1 to C 20carboxylic acid (e.g., 2-ethyl-hexyl carboxylic acid); aliphatic perfluorocarboxylic acid (e.g., trifluoroacetic acid or perfluorooctanoic acid); optionally C1 to C 20 Alkyl substituted aromatic sulfonic acids (e.g., benzenesulfonic acid, o-toluenesulfonic acid, p-toluenesulfonic acid, or dodecylbenzenesulfonic acid); cycloalkanesulfonic acids (e.g., camphorsulfonic acid or tetrafluoroborate, hexafluorophosphate, perchlorate, hexafluoroantimonate, hexafluoroarsenate, or hexachloroantimonate); and the like. Particularly suitable counter anions are polymeric anions, such as polymeric carboxylic acids or polymeric sulfonic acids (e.g., polystyrenesulfonic acid ("PSS")). The molecular weight of such polymeric anions is typically in the range of about 1,000 to about 2,000,000, and in some embodiments, about 2,000 to about 500,000.

[0096] When used, it may be desirable that the non-intrinsic conductive polymer be applied in the form of a dispersion of prepolymerized conductive particles. Such particles typically have an average size (e.g., diameter) of about 1 nanometer to about 100 nanometers, about 2 nanometers to about 80 nanometers in some embodiments, and about 4 nanometers to about 50 nanometers in some embodiments. The diameter of the particles can be measured using known techniques, such as by ultracentrifugation, laser diffraction, etc. The shape of the particles can also vary. For example, in a particular embodiment, the particles are spherical. However, it should be understood that the present invention also contemplates other shapes, such as plates, rods, disks, rods, tubes, irregular shapes, etc. The concentration of particles in the dispersion can vary according to the desired viscosity of the dispersion and the specific manner in which the dispersion is applied to the capacitor element. However, typically, particles constitute about 0.1wt.% to about 10wt.% of the dispersion, about 0.4wt.% to about 5wt.% in some embodiments, and about 0.5wt.% to about 4wt.% in some embodiments.

[0097] The dispersion can also include one or more adhesives to further enhance the bonding properties of the polymer layer and also increase the stability of the particles in the dispersion. The adhesive can be organic, such as polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl chloride, polyvinyl acetate, polyvinyl butyrate, polyacrylate, polyacrylamide, polymethacrylate, polymethacrylamide, polyacrylonitrile, styrene / acrylate, vinyl acetate / acrylate and ethylene / vinyl acetate copolymers, polybutadiene, polyisoprene, polystyrene, polyether, polyester, polycarbonate, polyurethane, polyamide, polyimide, polysulfone, melamine formaldehyde resin, epoxy resin, silicone resin or cellulose. Crosslinking agents can also be used to enhance the adhesion of adhesives. Such crosslinking agents can, for example, include melamine compounds, blocked (masked) isocyanates or functionalized silanes (such as, 3-glycidoxypropyltrialkoxysilane, tetraethoxysilane and tetraethoxysilane hydrolyzate) or crosslinked polymers (such as, polyurethane, polyacrylate or polyolefin), and subsequent crosslinking.

[0098] Dispersants can also be used to facilitate the ability to apply the layer to the anode. Suitable dispersants include solvents such as aliphatic alcohols (e.g., methanol, ethanol, isopropanol and butanol), aliphatic ketones (e.g., acetone and methyl ethyl ketone), aliphatic carboxylates (e.g., ethyl acetate and butyl acetate), aromatic hydrocarbons (e.g., toluene and xylene), aliphatic hydrocarbons (e.g., hexane, heptane and cyclohexane), chlorinated hydrocarbons (e.g., methylene chloride and ethylene dichloride), aliphatic nitriles (e.g., acetonitrile), aliphatic sulfoxides and sulfones (e.g., dimethyl sulfoxide and cyclopentane), aliphatic carboxylic acid amides (e.g., methylacetamide, dimethylacetamide and dimethylformamide), aliphatic and araliphatic ethers (e.g., diethyl ether and anisole), water, and mixtures of any of the foregoing solvents. Particularly suitable dispersants are water.

[0099] In addition to those mentioned above, other ingredients can also be used in the dispersion. For example, conventional fillers can be used, the size of which is from about 10 nanometers to about 100 microns, from about 50 nanometers to about 50 microns in some embodiments, and from about 100 nanometers to about 30 microns in some embodiments. Examples of such fillers include calcium carbonate, silicates, silicon oxide, calcium sulfate or barium sulfate, aluminum hydroxide, glass fibers or glass balls (bulb), wood powder, cellulose powder carbon black, conductive polymers, etc. Fillers can be introduced into the dispersion in powder form, but can also exist in other forms (e.g., fibers).

[0100] Surface-active substances such as ionic or nonionic surfactants may also be used in the dispersion. In addition, binders such as organofunctional silanes or their hydrolysis products, such as 3-glycidoxypropyltrialkoxysilane, 3-aminopropyl-triethoxysilane, 3-mercaptopropyl-trimethoxysilane, 3-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane or octyltriethoxysilane, may be used. The dispersion may also contain additives to increase conductivity, such as compounds containing ether groups (e.g., tetrahydrofuran), compounds containing lactone groups (e.g., γ-butyrolactone or γ-valerolactone), compounds containing amide groups or lactam groups (e.g., caprolactam, N-methylcaprolactam, N,N-dimethylacetamide, N-methylacetamide, N,N-dimethylformamide (DMF), N-methylformamide, N-methylformanilide, N-methylpyrrolidone (N -methylpyrrolidone, NMP), N-octylpyrrolidone or pyrrolidone), sulfones and sulfoxides (e.g., sulfolane (tetramethylene sulfone) or dimethylsulfoxide (DMSO)), sugars or sugar derivatives (e.g., sucrose, glucose, fructose or lactose), sugar alcohols (e.g., sorbitol or mannitol), furan derivatives (e.g., 2-furancarboxylic acid or 3-furancarboxylic acid), alcohols (e.g., ethylene glycol, glycerol, diethylene glycol or triethylene glycol).

[0101] The dispersion can be applied using various known techniques, for example by spin coating, dipping, pouring, dropwise application, injection, spraying, doctor blade coating, brushing, printing (e.g., inkjet printing, screen printing or pad printing) or immersion. The viscosity of the dispersion is typically from about 0.1 mPas to about 100,000 mPas (at 100 s -1 ), in some embodiments from about 1 mPas to about 10,000 mPas, in some embodiments from about 10 mPas to about 1,500 mPas, and in some embodiments from about 100 mPas to about 1000 mPas.

[0102] If desired, hydroxyl-functionalized nonionic polymers may also be employed in the outer layer of the solid electrolyte. The term "hydroxyl-functionalized" generally refers to a compound comprising at least one hydroxyl functional group or capable of having such a functional group in the presence of a solvent. Without intending to be limited by theory, it is believed that the use of hydroxyl-functionalized polymers of a certain molecular weight can minimize the possibility of chemical decomposition at high voltages. For example, the molecular weight of the hydroxyl-functionalized polymer may be about 100 g to 10,000 g per mole, about 200 to 2,000 in some embodiments, about 300 to about 1,200 in some embodiments, and about 400 to about 800 in some embodiments.

[0103] For this purpose, usually any one of various hydroxyl-functionalized nonionic polymers can be adopted.For example, in one embodiment, the hydroxyl-functionalized polymer is a polyalkylene ether.Polyalkylene ether can include polyalkylene glycols (for example, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyepichlorohydrin, etc.), polyoxetane, polyphenylene oxide, polyether ketone, etc.Typically, polyalkylene ether is mainly a straight chain nonionic polymer with terminal hydroxyl groups.Particularly suitable are polyethylene glycol, polypropylene glycol and polytetramethylene glycol (polytetrahydrofuran), which are prepared by the addition polymerization of ethylene oxide, propylene oxide or tetrahydrofuran and water.Polyalkylene ether can be prepared by diols or polyols through polycondensation reaction. In particular, the diol component can be selected from: saturated or unsaturated, branched or unbranched aliphatic dihydroxy compounds containing 5 to 36 carbon atoms; or saturated or unsaturated, branched or unbranched aromatic dihydroxy compounds, for example, pentane-1,5-diol, hexane-1,6-diol, neopentyl glycol, bis-(hydroxymethyl)-cyclohexane, bisphenol A, dimer diol, hydrogenated dimer diol, or even mixtures of the mentioned diols. In addition, polyhydric alcohols can also be used in the polymerization reaction, for example including glycerol, diglycerol and polyglycerol, trimethylolpropane, pentaerythritol or sorbitol.

[0104] In addition to those mentioned above, other hydroxyl-functionalized nonionic polymers may also be used in the present invention. Some examples of such polymers include: ethoxylated alkylphenols; ethoxylated C6-C 24 Fatty alcohol or propoxylated C6-C 24 Fatty alcohol; having the general formula: CH3-(CH2) 10-16 -(O-C2H4) 1-25 -OH-containing polyethylene glycol alkyl ethers (e.g., octaethylene glycol monododecyl ether and pentaethylene glycol monododecyl ether); having the general formula: CH3-(CH2) 10-16 -(O-C3H6) 1-25 -OH polyoxypropylene glycol alkyl ether; having the following general formula: C8H17 -(C6H4)-(O-C2H4) 1-25 -OH polyoxyethylene glycol octylphenol ether (for example, Triton TM X-100); having the following general formula: C9H 19 -(C6H4)-(O-C2H4) 1-25 -OH polyoxyethylene glycol alkylphenol ether (e.g., nonoxynol-9); C8 to C 24 Polyoxyethylene glycol esters of fatty acids, such as polyoxyethylene glycol sorbitan alkyl esters (e.g., polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene (20) sorbitan monopalmitate, polyoxyethylene (20) sorbitan monostearate, polyoxyethylene (20) sorbitan monooleate, PEG-20 methyl glucose distearate, PEG-20 methyl glucose sesquistearate, PEG-80 castor oil, and PEG-20 castor oil, PEG-3 castor oil, PEG 600 dioleate, and PEG 400 dioleate) and polyoxyethylene glyceryl alkyl esters (e.g., polyoxyethylene-23 glyceryl laurate and polyoxyethylene-20 glyceryl stearate); C8 to C 24 Polyoxyethylene glycol ethers of fatty acids (e.g., polyoxyethylene-10 cetyl ether, polyoxyethylene-10 stearyl ether, polyoxyethylene-20 cetyl ether, polyoxyethylene-10 oleyl ether, polyoxyethylene-20 oleyl ether, polyoxyethylene-20 isocetyl ether, polyoxyethylene-15 tridecyl ether, and polyoxyethylene-6 tridecyl ether); block copolymers of polyethylene glycol and polypropylene glycol (e.g., Poloxamers); and the like, and mixtures thereof.

[0105] Hydroxyl functionalized nonionic polymers can be incorporated into the outer layer in various ways. For example, in certain embodiments, the nonionic polymer can be simply incorporated into a dispersion of a non-intrinsic conductive polymer. In such embodiments, the concentration of the nonionic polymer in the layer can be from about 1wt.% to about 50wt.%, from about 5wt.% to about 40wt.% in some embodiments, and from about 10wt.% to about 30wt.% in some embodiments. However, in other embodiments, the nonionic polymer can be applied after the initial outer layer is formed. In such embodiments, the technology for applying the nonionic polymer can vary. For example, the nonionic polymer can be applied in the form of a liquid solution using various methods, such as dipping, immersion, pouring, dripping, injection, spraying, spreading, coating or printing (e.g., inkjet printing, screen printing or pad printing). In this solution, solvents known to those skilled in the art can be used, such as water, alcohol or a mixture thereof. In such a solution, the concentration of the nonionic polymer is typically about 5 wt.% to about 95 wt.% of the solution, in some embodiments about 10 wt.% to about 70 wt.%, and in some embodiments about 15 wt.% to about 50 wt.%. If desired, such a solution may generally be free of a conductive polymer. For example, a conductive polymer may constitute about 2 wt.% or less of the solution, in some embodiments about 1 wt.% or less, and in some embodiments about 0.5 wt.% or less.

[0106] E. External polymer coating

[0107] If desired, an external polymer coating can also be applied to the anode covered on the solid electrolyte. When used, the external polymer coating generally comprises one or more layers formed by conductive polymer particles such as those described above (for example, formed by non-intrinsic conductive polymers). The external coating may be able to further penetrate into the edge region of the capacitor body to increase the adhesion to the dielectric and produce a more mechanically stable (robust) component, which can reduce equivalent series resistance and leakage current. Because the external coating is generally intended to improve the edge coverage rather than immersing the inside of the anode body, the particles used in the external coating may have a larger size than those used in the optional particles used in the solid electrolyte (for example, in the outer layer). For example, the average size of the particles used in the external polymer coating is typically about 1.5 to about 30, about 2 to about 20 in some embodiments, and about 5 to about 15 in some embodiments. For example, the average size of the particles used in the external coating is about 50 nanometers to about 800 nanometers, about 80 nanometers to about 600 nanometers in some embodiments, and about 100 nanometers to about 500 nanometers in some embodiments.

[0108] A crosslinking agent may also be employed in the outer polymer coating to improve adhesion to the solid electrolyte. Typically, the crosslinking agent is applied prior to application of the dispersion used in the outer coating. Suitable crosslinking agents are described, for example, in Merker et al. The invention relates to a catalytic oxidation of ...

[0109] The crosslinking agent is typically applied from a solution or dispersion having a pH of 1 to 10, in some embodiments 2 to 7, and in some embodiments 3 to 6, measured at 25°C. Acidic compounds may be used to help achieve the desired pH level. Examples of solvents or dispersants for the crosslinking agent include water or organic solvents such as alcohols, ketones, carboxylates, and the like. The crosslinking agent may be applied to the capacitor body by any known process, such as spin coating, dipping, pouring, dropwise application, spraying, vapor deposition, sputtering, sublimation, scraping, brushing, or printing (e.g., inkjet printing, screen printing, or pad printing). Once applied, the crosslinking agent may be dried before applying the polymer dispersion. The process may then be repeated until the desired thickness is obtained. For example, the total thickness of the entire outer polymer coating (including the crosslinking agent and dispersion layer) may be from about 1 μm to about 50 μm, from about 2 μm to about 40 μm in some embodiments, and from about 5 μm to about 20 μm in some embodiments.

[0110] F. Cathodic coating

[0111] If desired, the capacitor element can also be provided with a cathode coating overlying the solid electrolyte and the outer polymer coating. The cathode coating can contain a metal particle layer comprising a plurality of conductive metal particles dispersed in a polymer matrix. The particles typically constitute about 50 wt.% to about 99 wt.%, in some embodiments about 60 wt.% to about 98 wt.%, and in some embodiments about 70 wt.% to about 95 wt.%, of the layer, while the polymer matrix typically constitutes about 1 wt.% to about 50 wt.%, in some embodiments about 2 wt.% to about 40 wt.%, and in some embodiments about 5 wt.% to about 30 wt.%.

[0112] Conductive metal particles can be formed from various metals (such as copper, nickel, silver, nickel, zinc, tin, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium, etc., and their alloys). Silver is a particularly suitable conductive metal for this layer. The metal particles generally have a relatively small size, such as an average size of about 0.01 micron to about 50 microns, about 0.1 micron to about 40 microns in some embodiments, and about 1 micron to about 30 microns in some embodiments. Typically, only one metal particle layer is used, but it should be understood that multiple layers can be used if desired. The total thickness of such layers typically ranges from about 1 μm to about 500 μm, from about 5 μm to about 200 μm in some embodiments, and from about 10 μm to about 100 μm in some embodiments.

[0113] The polymer matrix typically comprises a polymer, which may be a thermoplastic or a thermoset. However, the polymer is typically selected so that it can act as a barrier to the electromigration of silver ions and also so that it contains a relatively small number of polar groups, thereby making the cathode Coating In this regard, the present inventors have found that vinyl acetal polymers (such as polyvinyl butyral, polyvinyl formal, etc.) are particularly suitable for this purpose. For example, polyvinyl butyral can be formed by reacting polyvinyl alcohol with aldehyde (e.g., butyraldehyde). Since the reaction is typically incomplete, polyvinyl butyral usually has a residual hydroxyl content. However, by minimizing the content, the polymer can have a small degree of strong polar groups, otherwise the strong polar groups can cause a high degree of moisture adsorption and cause silver ion migration. For example, the residual hydroxyl content in polyvinyl acetal can be about 35mol.% or less, about 30mol.% or less in some embodiments, and about 10mol.% to about 25mol.% in some embodiments. A commercially available embodiment of this type of polymer can be obtained from Sekisui Chemical Co., Ltd. under the name "BH-S" (polyvinyl butyral).

[0114] To form the cathode coating, a conductive slurry is typically applied to the capacitor overlying the solid electrolyte. One or more organic solvents are typically employed in the slurry. Generally, various organic solvents can be used, such as glycols (e.g., propylene glycol, butylene glycol, triethylene glycol, hexylene glycol, polyethylene glycol, ethoxydiethylene glycol and dipropylene glycol), glycol ethers (e.g., methyl glycol ether, ethyl glycol ether and isopropyl glycol ether), ethers (e.g., diethyl ether and tetrahydrofuran), alcohols (e.g., benzyl alcohol, methanol, ethanol, n-propanol, isopropanol and butanol), triglycerides, ketones (e.g., acetone, methyl ethyl ketone and methyl isobutyl ketone), esters (e.g., ethyl acetate, butyl acetate, diethylene glycol ether acetate and methoxypropyl acetate), amides (e.g., dimethylformamide, dimethylacetamide, dimethyl octanyl / decyl fatty acid amide and N-alkylpyrrolidone), nitriles (e.g., acetonitrile, propionitrile, butyronitrile and benzonitrile), sulfoxides or sulfones (e.g., dimethyl sulfoxide (DMSO) and sulfolane), and the like, and mixtures thereof. The organic solvent generally constitutes about 10 wt.% to about 70 wt.% of the slurry, in some embodiments, about 20 wt.% to about 65 wt.%, and in some embodiments, about 30 wt.% to about 60 wt.%. Typically, the metal particles constitute about 10 wt.% to about 60 wt.% of the slurry, in some embodiments, about 20 wt.% to about 45 wt.%, and in some embodiments, about 25 wt.% to about 40 wt.%, and the resinous matrix constitutes about 0.1 wt.% to about 20 wt.%, in some embodiments, about 0.2 wt.% to about 10 wt.%, and in some embodiments, about 0.5 wt.% to about 8 wt.%.

[0115] The slurry can have a relatively low viscosity, making it easy to handle and apply to capacitor elements. For example, the viscosity can be about 50 centipoise to about 3,000 centipoise, about 100 centipoise to about 2,000 centipoise in some embodiments, and about 200 centipoise to about 1,000 centipoise in some embodiments, such as measured by operating a Brookfield Dv-1 viscometer (cone and plate) at a speed of 10rpm and a temperature of 25°C. If desired, a thickener or other viscosity modifier can be used in the slurry to increase or reduce viscosity. In addition, the thickness of the applied slurry can also be relatively thin and still achieve the desired properties. For example, the thickness of the slurry can be about 0.01 micron to about 50 microns, about 0.5 micron to about 30 microns in some embodiments, and about 1 micron to about 25 microns in some embodiments. When applied, the metal slurry can be optionally dried to remove certain components, such as organic solvents. For example, drying may occur at a temperature of from about 20°C to about 150°C, in some embodiments, from about 50°C to about 140°C, and in some embodiments, from about 80°C to about 130°C.

[0116] G. Other Components

[0117] If desired, the capacitor may also contain other layers known in the art. In certain embodiments, for example, a carbon layer (e.g., graphite) may be positioned between the solid electrolyte and the silver layer, which may help further limit the contact of the silver layer with the solid electrolyte. In addition, a pre-coating layer may also be employed, which is overlying the dielectric and includes an organometallic compound.

[0118] II. terminal

[0119] Once formed, the capacitor element can be provided with a terminal, especially when used in surface mounting applications. For example, the capacitor can include an anode terminal and a cathode terminal, the anode terminal is electrically connected to the anode lead of the capacitor element, and the cathode terminal is electrically connected to the cathode of the capacitor element. Any conductive material can be used to form the terminal, such as a conductive metal (for example, copper, nickel, silver, nickel, zinc, tin, palladium, lead, copper, aluminum, molybdenum, titanium, iron, zirconium, magnesium and their alloys). Particularly suitable conductive metals include, for example, copper, copper alloys (for example, copper-zirconium, copper-magnesium, copper-zinc or copper-iron), nickel and nickel alloys (for example, nickel-iron). The thickness of the terminal is usually selected to minimize the thickness of the capacitor. For example, the thickness of the terminal can range from about 0.05 millimeters to about 1 millimeter, from about 0.05 millimeters to about 0.5 millimeters in some embodiments, and from about 0.07 millimeters to about 0.2 millimeters. An exemplary conductive material is a copper-iron alloy metal plate that can be obtained from Wieland (Wieland, Germany). If desired, the surface of the terminal can be plated with nickel, silver, gold, tin, etc. as known in the art to ensure that the final component can be mounted to the circuit board. In a specific embodiment, the two surfaces of the terminal are plated with a nickel flash layer and a silver flash layer, respectively, and the mounting surface is also plated with a tin solder layer.

[0120] The terminals can be connected to the capacitor element using any technique known in the art. For example, in one embodiment, a lead frame defining a cathode terminal and an anode terminal can be provided. In order to attach the electrolytic capacitor element to the lead frame, a conductive adhesive can first be applied to the surface of the cathode terminal. For example, the conductive adhesive can include conductive metal particles containing a resin composition. The metal particles can be silver, copper, gold, platinum, nickel, zinc, bismuth, etc. The resin composition can include a thermosetting resin (e.g., an epoxy resin), a curing agent (e.g., anhydride), and a coupling agent (e.g., a silane coupling agent). Suitable conductive adhesives can be used in Osako et al.The conductive adhesive may be applied to the cathode terminal using any of a variety of techniques. For example, printing techniques may be used due to their practical and cost-effective advantages. The anode lead may also be electrically connected to the anode terminal using any technique known in the art (such as mechanical welding, laser welding, conductive adhesives, etc.). Once the anode lead is electrically connected to the anode terminal, the conductive adhesive may be cured to ensure that the electrolytic capacitor element is adequately adhered to the cathode terminal.

[0121] III. case

[0122] Capacitor element can be incorporated into the housing in various ways. For example, in certain embodiments, capacitor element is encapsulated in a case, and then, the case can be filled with a resin material such as a thermosetting resin (e.g., epoxy resin), which can be cured to form a hardened housing. The resin material can surround and encapsulate capacitor element, exposing at least a portion of anode terminal and cathode terminal for installation on a circuit board. When encapsulated in this way, capacitor element and resin material form an integrated capacitor.

[0123] Of course, in alternative embodiments, it may be desirable to encapsulate capacitor elements in separate and different housings. In this manner, the atmosphere of the housing can be selectively controlled to dry the housing, which limits the humidity that can contact the capacitor elements. For example, the moisture content of the atmosphere (expressed as relative humidity) can be about 10% or less, about 5% or less in some embodiments, about 3% or less in some embodiments, and about 0.001% to about 1% in some embodiments. For example, the atmosphere of the housing can be gaseous and contain at least one inert gas, such as nitrogen, helium, argon, xenon, neon, krypton, radon, etc., and mixtures thereof. Typically, inert gases constitute most of the atmosphere in the housing, such as about 50wt.% to 100wt.% of the atmosphere, about 75wt.% to 100wt.% in some embodiments, and about 90wt.% to about 99wt.% in some embodiments. If desired, relatively small amounts of non-inert gases, such as carbon dioxide, oxygen, water vapor, etc., can also be used. However, in such cases, the non-inert gas typically constitutes 15 wt.% or less, in some embodiments, about 10 wt.% or less, in some embodiments, about 5 wt.% or less, in some embodiments, about 1 wt.% or less, and in some embodiments, from about 0.01 wt.% to about 1 wt.% of the atmosphere within the housing.

[0124] The housing may be formed using any of a variety of different materials, such as metals, plastics, ceramics, etc. For example, in one embodiment, the housing includes one or more layers of metals, such as tantalum, niobium, aluminum, nickel, hafnium, titanium, copper, silver, steel (e.g., stainless steel), alloys thereof (e.g., conductive oxides), composites thereof (e.g., metals coated with conductive oxides), etc. In another embodiment, the housing may include one or more layers of ceramic materials, such as aluminum nitride, aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, glass, etc., and combinations thereof.

[0125] The housing may have any desired shape, such as cylindrical, D-shaped, rectangular, triangular, prismatic, etc. For example, referring to Figure 1 , shows an embodiment of a capacitor 100 that includes a housing 122 and a capacitor element 120. In this particular embodiment, the housing 122 is generally rectangular. Typically, the housing and the capacitor element have the same or similar shapes so that the capacitor element can be easily accommodated in the internal cavity. For example, in the embodiment shown, both the capacitor element 120 and the housing 122 have a generally rectangular shape.

[0126] If desired, the capacitor of the present invention can present relatively high volumetric efficiency. In order to promote such high efficiency, capacitor element typically occupies a considerable part of the internal chamber volume of the housing. For example, capacitor element can occupy about 30vol.% or higher of the internal chamber of the housing, about 50vol.% or higher in some embodiments, about 60vol.% or higher in some embodiments, about 70vol.% or higher in some embodiments, about 80vol.% to about 98vol.% in some embodiments, and about 85vol.% to 97vol.% in some embodiments. For this reason, the difference between the size of the capacitor element and the size of the internal chamber defined by the housing is usually relatively small.

[0127] For example, refer to Figure 1, the capacitor element 120 has a length (excluding the length of the anode lead 6) that can be relatively similar to the length of the internal chamber 126 defined by the housing 122. For example, the ratio of the length of the anode to the length of the internal chamber ranges from about 0.40 to 1.00, in some embodiments, from about 0.50 to about 0.99, in some embodiments, from about 0.60 to about 0.99, and in some embodiments, from about 0.70 to about 0.98. The length of the capacitor element 120 can be from about 5 mm to about 10 mm, and the length of the internal chamber 126 can be from about 6 mm to about 15 mm. Similarly, the ratio of the height (in the z direction) of the capacitor element 120 to the height of the internal chamber 126 can range from about 0.40 to 1.00, in some embodiments, from about 0.50 to about 0.99, in some embodiments, from about 0.60 to about 0.99, and in some embodiments, from about 0.70 to about 0.98. The ratio of the width (in the x-direction) of capacitor element 120 to the width of interior chamber 126 can range from about 0.50 to 1.00, in some embodiments from about 0.60 to about 0.99, in some embodiments from about 0.70 to about 0.99, in some embodiments from about 0.80 to about 0.98, and in some embodiments from about 0.85 to about 0.95. For example, the width of capacitor element 120 can be about 2 mm to about 7 mm, and the width of interior chamber 126 can be about 3 mm to about 10 mm, the height of capacitor element 120 can be about 0.5 mm to about 2 mm, and the width of interior chamber 126 can be about 0.7 mm to about 6 mm.

[0128] Although absolutely not necessary, the capacitor element can be attached to the housing in the following manner: the anode terminal and the cathode terminal are formed on the outside of the housing so as to be subsequently integrated into the circuit. The specific configuration of the terminal can depend on the intended application. For example, in one embodiment, a capacitor can be formed so that the capacitor is surface mountable and mechanically stable. For example, the anode lead can be electrically connected to external, surface mountable anode and cathode terminals (e.g., pads, sheets, plates, frames, etc.). Such terminals can extend through the housing to be connected to the capacitor. The thickness or height of the terminal is usually selected to minimize the thickness of the capacitor. For example, the thickness of the terminal can range from about 0.05 mm to about 1 mm, from about 0.05 mm to about 0.5 mm in some embodiments, and from about 0.1 mm to about 0.2 mm. If desired, the surface of the terminal can be electroplated with nickel, silver, gold, tin, etc. as known in the art to ensure that the final component can be mounted to the circuit board. In a specific embodiment, the terminal is deposited with a nickel flash layer and a silver flash layer, and the mounting surface is also plated with a tin solder layer. In another embodiment, the terminals have a thin outer metal layer (eg, gold) deposited on a base metal layer (eg, copper alloy) to further improve conductivity.

[0129] In certain embodiments, a connective member may be employed within the interior chamber of the housing to facilitate connection to the terminals in a mechanically stable manner. Figure 1 , the capacitor 100 may include a connecting member 162 formed by a first portion 167 and a second portion 165. The connecting member 162 can be formed of a conductive material similar to the external terminals. The first portion 167 and the second portion 165 can be integrated or separate parts connected together directly or via an additional conductive element (e.g., metal). In the illustrated embodiment, the second portion 165 is disposed in a plane that is substantially parallel to the lateral direction (e.g., y-direction) in which the lead 6 extends. The first portion 167 is "upright" in the sense that the first portion 167 is disposed in a plane that is substantially perpendicular to the lateral direction in which the lead 6 extends. In this manner, the first portion 167 can limit the movement of the lead 6 in the horizontal direction to enhance surface contact and mechanical stability during use. If desired, an insulating material 7 (e.g., Teflon) can be used around the lead 6. TM washer).

[0130] The first portion 167 may have a mounting region (not shown) that is connected to the anode lead 6. The region may have a "U-shape" to further enhance the surface contact and mechanical stability of the lead 6. The connection of the region to the lead 6 may be achieved using any of a variety of known techniques, such as welding, laser welding, conductive adhesives, etc. For example, in a particular embodiment, the region is laser welded to the anode lead 6. However, no matter which technique is selected, the first portion 167 is able to maintain the anode lead 6 in a substantially horizontal alignment to further enhance the dimensional stability of the capacitor 100.

[0131] Reference again Figure 1 , shows an embodiment of the present invention, wherein the connection member 162 and the capacitor element 120 are connected to the housing 122 by the anode terminal 127 and the cathode terminal 129, respectively. More specifically, the housing 122 of this embodiment includes an outer wall 123 and two opposite side walls 124, between which a chamber 126 including the capacitor element 120 is formed. The outer wall 123 and the side wall 124 can be formed by one or more layers of metal, plastic, or ceramic materials such as those described above. In this particular embodiment, the anode terminal 127 includes a first region 127a located inside the housing 122 and electrically connected to the connection member 162, and a second region 127b located outside the housing 122 and providing a mounting surface 201. Similarly, the cathode terminal 129 includes a first region 129a located inside the housing 122 and electrically connected to the solid electrolyte of the capacitor element 120, and a second region 129b located outside the housing 122 and providing a mounting surface 203. It should be understood that the entire portion of such an area does not need to be located inside or outside the housing.

[0132] In the illustrated embodiment, conductive trace 127c extends in the outer wall 123 of the housing to connect the first region 127a and the second region 127b. Similarly, conductive trace 129c extends in the outer wall 123 of the housing to connect the first region 127a and the second region 127b. The conductive traces and / or terminal regions can be separate or integrated. In addition to extending through the outer wall of the housing, the traces can also be located at other locations, such as outside the outer wall. Of course, the present invention is by no means limited to using conductive traces to form desired terminals.

[0133] Regardless of the particular configuration, the connection of the terminals 127 and 129 to the capacitor element 120 may be made using any known technique (e.g., welding, laser welding, conductive adhesives, etc.). For example, in one particular embodiment, a conductive adhesive 131 is used to connect the second portion 165 of the connecting member 162 to the anode terminal 127. Similarly, a conductive adhesive 133 is used to connect the cathode of the capacitor element 120 to the cathode terminal 129.

[0134] Optionally, the polymeric constraint may also be arranged to contact one or more surfaces of the capacitor element, such as a rear surface, a front surface, an upper surface, a lower surface, a side surface, or any combination thereof. The polymeric constraint can reduce the likelihood of the capacitor element delaminating from the housing. In this regard, the polymeric constraint may have a degree of strength that allows the polymeric constraint to maintain the capacitor element in a relatively fixed position even when subjected to vibration forces, but the strength is not strong enough to cause the capacitor element to rupture. For example, the constraint may have a tensile strength of about 1 megapascal to about 150 megapascals ("MPa") measured at a temperature of about 25°C, about 2 MPa to about 100 MPa in some embodiments, about 10 MPa to about 80 MPa in some embodiments, and about 20 MPa to about 70 MPa in some embodiments. It is generally desired that the constraint is non-conductive. For example, again referring to Figure 1 , shows an embodiment in which a single polymeric constraint 197 is disposed in contact with the upper surface 181 and the rear surface 177 of the capacitor element 120. Although Figure 1 In the figure, a single constraint is shown, but it should be understood that a separation constraint can be used to achieve the same function. In fact, more generally, any desired surface of the capacitor element can be contacted by any number of polymer constraints. When multiple constraints are used, they can contact each other or remain physically separated. For example, in one embodiment, the upper surface 181 of the contact capacitor element 120 and the second polymer constraint (not shown) of the front surface 179 can be used. The first polymer constraint 197 and the second polymer constraint (not shown) can contact each other or may not contact each other. In another embodiment, the polymer constraint can also contact the lower surface 183 and / or the side surface of the capacitor element 120 together with or instead of other surfaces.

[0135] Regardless of how the polymeric restraint is applied, it is typically desirable that the polymeric restraint also be in contact with at least one surface of the housing to help further mechanically stabilize the capacitor element against possible delamination. For example, the restraint may be in contact with the interior surface of one or more sidewalls, outer walls, lids, etc. For example, in Figure 1In the embodiment of the present invention, the polymeric constraint 197 is in contact with the inner surface 107 of the side wall 124 and the inner surface 109 of the outer wall 123. Even so, when in contact with the shell, it is desirable that at least a portion of the chamber defined by the shell remain unoccupied to allow the inert gas to flow through the chamber and limit the contact of the solid electrolyte with oxygen. For example, at least about 5% of the volume of the chamber, and in some embodiments about 10% to about 50% of the volume of the chamber typically remain unoccupied by the capacitor element and the polymeric constraint.

[0136] Once in the desired manner, the resulting package is hermetically sealed as described above. For example, again referring to Figure 1 , the housing 122 may also include a cover 125, which is placed on the upper surface of the side wall 124 after the capacitor element 120 and the polymer constraint 197 are positioned within the housing 122. The cover 125 may be formed of ceramic, metal (e.g., iron, copper, nickel, cobalt, etc., and alloys thereof), plastic, etc. If desired, a sealing member 187 may be disposed between the cover 125 and the side wall 124 to help provide a good seal. For example, in one embodiment, the sealing member may include a glass-metal seal, The height of the side wall 124 is typically such that the cover 125 does not contact any surface of the capacitor element 120 so that the cover is not contaminated. The polymeric constraint 197 may or may not contact the cover 125. When placed in the desired position, the cover 125 is hermetically sealed to the side wall 124 using known techniques, such as welding (e.g., resistance welding, laser welding, etc.), brazing, etc. Hermetically sealing typically occurs in the presence of an inert gas as described above, so that the resulting assembly is substantially free of reactive gases (such as oxygen or water vapor).

[0137] It should be understood that the described embodiments are exemplary only and that various other configurations may be employed in the present invention to hermetically seal the capacitor element within the housing. Figure 2, another embodiment of a capacitor 200 is shown, which employs a housing 222 including an outer wall 123 and a cover 225, between which a chamber 126 including a capacitor element 120 and a polymeric restraint 197 is formed. The cover 225 includes an outer wall 223 integrated with at least one side wall 224. For example, in the embodiment shown, two opposing side walls 224 are shown in cross section. The outer walls 223 and 123 both extend in a transverse direction (y-direction) and are generally parallel to each other and to the transverse direction of the anode lead 6. The side wall 224 extends from the outer wall 223 in a longitudinal direction that is generally perpendicular to the outer wall 123. The distal end 500 of the cover 225 is defined by the outer wall 223, and the proximal end 501 is defined by the flange 253 of the side wall 224.

[0138] The flange 253 extends from the side wall 224 in a lateral direction that can be substantially parallel to the lateral direction of the outer wall 123. The angle between the side wall 224 and the flange 253 can vary, but is typically about 60° to about 120°, in some embodiments about 70° to about 110°, and in some embodiments about 80° to about 100° (e.g., about 90°). The flange 253 also defines a peripheral edge 251 that can be substantially perpendicular to the lateral direction in which the flange 253 and the outer wall 123 extend. The peripheral edge 251 is located outside the periphery of the side wall 224 and can be substantially coplanar with the edge 151 of the outer wall 123. The flange 253 can be sealed to the outer wall 123 using any known technique, such as welding (e.g., resistance welding or laser welding), brazing, gluing, etc. For example, in the illustrated embodiment, a sealing member 287 (e.g., a glass-to-metal seal, In any case, the use of the above-mentioned flange can enable a more stable connection between components and improve the sealing and mechanical stability of the capacitor.

[0139] Other possible housing structures may also be used in the present invention. For example, Figure 3 shows a similar Figure 2 The capacitor 300 of the housing structure is constructed as shown in FIG. 32, but the terminal pins 327b and 329b are used as external terminals for the anode and cathode, respectively. More specifically, the terminal pin 327a extends through the trace 327c formed in the outer wall 323 and is connected to the anode lead 6 using a known technique (e.g., welding). The additional portion 327a can be used to stabilize the pin 327b. Similarly, the terminal pin 329b extends through the trace 329c formed in the outer wall 323 and is connected to the cathode via the conductive adhesive 133 as described above.

[0140] For only a single capacitor element, the Figure 1-Figure 3 However, it should also be understood that multiple capacitor elements may also be hermetically sealed within the housing. Multiple capacitor elements may be attached to the housing using any of a variety of different techniques. For example, referring to Figure 4 , a specific embodiment of a capacitor 400 comprising two capacitor elements is shown, and, now it will be described in more detail. More particularly, capacitor 400 includes a first capacitor element 420a electrically connected to a second capacitor element 420b. In this embodiment, the capacitor elements are aligned so that their major surfaces are in a horizontal configuration. That is to say, the major surface of the capacitor element 420a defined by its width (x direction) and length (y direction) is located at a position adjacent to the corresponding major surface of the capacitor element 420b. Therefore, the major surface is usually coplanar. Alternatively, the capacitor elements can be arranged so that their major surfaces are not coplanar, but perpendicular to each other in a certain direction (such as z direction or x direction). Of course, the capacitor elements do not need to extend in the same direction.

[0141] Capacitor elements 420a and 420b are located within a housing 422 that includes an outer wall 423 and side walls 424 and 425 that together define a chamber 426. Although not shown, a cover that covers the upper surfaces of side walls 424 and 425 and seals assembly 400 may be employed as described above. Optionally, a polymeric restraint may also be employed to help limit vibration of the capacitor elements. For example, in Figure 4 In the embodiment of the present invention, separated polymer constraints 497a and 497b are located adjacent to capacitor elements 420a and 420b and contact capacitor elements 420a and 420b respectively. Polymer constraints 497a and 497b can be located at various different positions. In addition, one of the constraints can be removed, or additional constraints can be used. For example, in certain embodiments, it may be desirable to use polymer type constraints between capacitor elements to further improve mechanical stability.

[0142] In addition to the capacitor elements, the capacitor also includes an anode terminal electrically connected to the anode lead of each capacitor element and a cathode terminal electrically connected to the cathode of each capacitor element. Figure 4, capacitor elements connected in parallel with a common cathode terminal 429 are shown. In this particular embodiment, cathode terminal 429 is initially disposed in a plane substantially parallel to the bottom surface of the capacitor element and may be in electrical contact with a conductive trace (not shown). Capacitor 400 also includes connecting members 427 and 527 connected to anode leads 407a and 407b of capacitor elements 420a and 420b, respectively. More particularly, connecting member 427 includes an upright portion 465 and a flat portion 463 connected to an anode terminal (not shown). Similarly, connector 527 includes an upright portion 565 and a flat portion 563 connected to an anode terminal (not shown). Of course, it should be understood that a variety of other types of connecting mechanisms may also be employed.

[0143] The present invention may be better understood with reference to the following examples.

[0144] Testing Procedure

[0145] capacitance

[0146] Capacitance was measured using a Keithley 3330 Precision LCZ meter with Kelvin Leads, 2.2 volt DC bias and 0.5 volt peak to peak sinusoidal signal. The operating frequency was 120 Hz and the temperature was 23°C. + 2℃.

[0147] Breakdown voltage

[0148] Using Keithley 2400 SourceMeter at 23°C + The breakdown voltage is measured at a temperature of 2°C. Each capacitor can be charged with a constant current determined by the following equation:

[0149] Current (A) = nominal capacitance (F) × dU / dt,

[0150] Where dU / dt represents the voltage slope and is typically set to 10 V / s. The voltage is measured during charging and the maximum voltage value reached when the applied voltage drops by more than 10% is recorded as the breakdown voltage.

[0151] Equivalent Series Resistance (ESR)

[0152] The equivalent series resistance can be measured using a Keithley 3330 Precision LCZ meter with Kelvin leads, with a 2.2 volt DC bias and a 0.5 volt peak-to-peak sinusoidal signal. The operating frequency is 100 kHz and the temperature is 23°C. + 2℃.

[0153] Dissipation coefficient

[0154] The dissipation factor can be measured using a Keithley 3330 Precision LCZ meter with Kelvin leads, with a 2.2 volt DC bias and a 0.5 volt peak-to-peak sinusoidal signal. The operating frequency can be 120 Hz and the temperature can be 23°C. + 2℃.

[0155] Leakage Current

[0156] You can use a leakage tester at 23°C + The leakage current is measured at a temperature of 3°C and at rated voltage after a minimum of 60 seconds.

[0157] Surge voltage test

[0158] Can be at 85℃ + Surge voltage testing is performed (10-25 parts) at a temperature of 3°C and 1.3 times the rated voltage (e.g., 45.5V). The resistor used in the test circuit can be 33 ohms. Each cycle includes a 30-second surge voltage application followed by a 30-second discharge cycle. The test samples are dried at 125°C for at least 12 hours before testing. After the recovery time, the capacitance can be measured at every 1,000 pulse cycles up to 5,000 pulses.

[0159] Dielectric thickness

[0160] Dielectric thickness can be measured using a Zeiss Sigma FESEM at 20,000x to 50,000x magnification. The sample can be prepared by cutting the finished part in a plane perpendicular to the longest dimension of the finished part. The thickness measurement can be made at a location through the dielectric layer in a direction perpendicular to the cut.

[0161] Example 1

[0162] Anode samples were formed using 40,000 μFV / g tantalum powder. Each anode sample was embedded with tantalum wire, sintered at 1440°C, and pressed to 5.1 g / cm 3The pellets were anodized to 81.0 volts at a temperature of 40°C in a water / phosphoric acid electrolyte having a conductivity of 8.6 mS to form a dielectric layer. The pellets were anodized again to 150 volts for 15 seconds at a temperature of 30°C in a water / boric acid / disodium tetraborate having a conductivity of 2.0 mS to form a thicker oxide layer built on the exterior. A conductive polymer coating was formed by immersing the anode in a solution of poly 3-[(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propane-sulfonic acid. Once coated, the parts were dried at 125°C for 15 minutes. The process was repeated 7 times. Afterwards, the parts were immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios TM K, Heraeus). Once coated, the parts were dried at 125°C for 15 minutes. This process was repeated 8 times. Afterwards, the parts were immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios TM K, Heraeus). Once coated, the parts were dried at 125°C for 15 minutes. This process was repeated 3 times. Afterwards, the parts were immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios TM K, Heraeus). Once coated, the parts were dried at 125°C for 15 minutes. This process was repeated 14 times. The parts were then immersed in a graphite dispersion and dried. Finally, the parts were immersed in a silver dispersion and dried. In this way, multiple parts (500) of 47μF / 35V capacitors were manufactured and encapsulated in silica resin.

[0163] Example 2

[0164] The capacitors were formed in the manner described in Example 1, except that four pre-coatings of an organometallic compound containing an ethanol solution (1.0%) of (3-aminopropyl)trimethoxysilane were used, and different conductive polymer coatings were used. That is, the conductive polymer coating was formed by immersing the anode in a solution of poly 3-[(2,3-dihydrothieno-[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propane-sulfonic acid. Once coated, the parts were dried at 125° C. for 15 minutes. This process was repeated 6 times. Thereafter, the parts were immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios 200 wt %) having a solid content of 1.1% and a viscosity of 20 mPa.s. TMK, Heraeus). Once coated, the parts were dried at 125°C for 15 minutes. This process was repeated 8 times. Afterwards, the parts were immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios TM K, Heraeus). Once coated, the parts were dried at 125°C for 15 minutes. This process was repeated 3 times. Afterwards, the parts were immersed in a dispersed poly(3,4-ethylenedioxythiophene) (Clevios TM K, Heraeus). Once coated, the parts were dried at 125°C for 15 minutes. This process was repeated 14 times. The parts were then immersed in a graphite dispersion and dried. Finally, the parts were immersed in a silver dispersion and dried. In this way, multiple parts (500) of 47μF / 35V capacitors were manufactured and encapsulated in silica resin.

[0165] The median capacitance results after the surge voltage test are shown in Table 1 below.

[0166] Table 1: Surge voltage test results

[0167]

[0168] Without departing from the spirit and scope of the present invention, those of ordinary skill in the art may implement these and other modifications and variations of the present invention. In addition, it should be understood that the various aspects of the various embodiments may be interchangeable in whole or in part. In addition, those of ordinary skill in the art will appreciate that the foregoing description is only exemplary and is not intended to limit the present invention further described in these appended claims.

Claims

1. A solid electrolytic capacitor, comprising a capacitor element, wherein: The capacitor element comprises: Anode body; A dielectric, the dielectric covering the anode body; a pre-coating layer, the pre-coating layer covering the anode body, wherein the pre-coating layer is formed of an organic metal compound; and A solid electrolyte, the solid electrolyte is coated on the dielectric, wherein the solid electrolyte includes at least one inner layer, the inner layer is coated on the pre-coating layer, the inner layer does not contain a non-intrinsic conductive polymer, and includes an intrinsic conductive polymer, and the intrinsic conductive polymer includes repeating thiophene units of the following general formula (I): in, a is 0 to 10; b is 1 to 18; R is an optionally substituted C1-C6 straight chain or branched alkyl group or a halogen atom; and M is a hydrogen atom, an alkali metal, NH(R 1 )3, or HNC5H5, wherein R 1 Each is independently a hydrogen atom or an optionally substituted C1-C6 alkyl group; wherein the solid electrolyte comprises at least one outer layer, wherein the outer layer is formed of particles comprising polymeric counterions and an extrinsic conductive polymer; and The capacitor exhibits a charge-discharge capacitance after being subjected to 5000 surge voltage cycles, and the capacitor exhibits an initial capacitance before being subjected to 5000 surge voltage cycles, wherein a ratio of the charge-discharge capacitance to the initial capacitance is 0.9 to 1.

2. The solid electrolytic capacitor according to claim 1, wherein: a is 1 and b is 3 or 4.

3. The solid electrolytic capacitor according to claim 1, wherein: R is methyl.

4. The solid electrolytic capacitor according to claim 1, wherein: M is an alkali metal.

5. The solid electrolytic capacitor according to claim 1, wherein: The repeating thiophene unit is formed by: sodium 3-[(2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-propyl-1-propanesulfonate, sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-ethyl-1-propanesulfonate Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-butyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-pentyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-hexyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopropyl-1-propanesulfonate Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isobutyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-fluoro-1-propanesulfonate, Sodium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-isopentyl-1-propanesulfonate 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonic acid, ammonium 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, triethylamine 3-[(2,3-dihydrothieno[3,4-b]-[1,4]dioxin-2-yl)methoxy]-1-methyl-1-propanesulfonate, or a combination thereof.

6. The solid electrolytic capacitor according to claim 1, wherein: The specific conductivity of the polymer was 20 S / cm.

7. The solid electrolytic capacitor according to claim 1, wherein: The outer layer comprises a hydroxyl-functional nonionic polymer.

8. The solid electrolytic capacitor according to claim 1, wherein: The organometallic compound is a monoamino-functional silane having the following general formula (II): in, R1, R2 and R3 are independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl or hydroxyalkyl; R4 and R5 are independently hydrogen, alkyl, independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl, hydroxyalkyl, or N, and R4 and R5 together with one or more additional atoms form a ring structure; and Z is an organic group.

9. The solid electrolytic capacitor according to claim 8, wherein: The monoamino-functional silane is a primary amine.

10. The solid electrolytic capacitor according to claim 9, wherein: The primary amine is 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 4-aminobutyltriethoxysilane, m-aminophenyltrimethoxysilane, p-aminophenyltrimethoxysilane, aminophenyltrimethoxysilane, 3-aminopropyltri(methoxy-ethoxy)silane, 11-aminoundecyltriethoxysilane, 2(4-pyridylethyl)triethoxysilane, 2-(trimethoxysilylethyl)pyridine, N-(3-trimethoxysilylpropyl)pyrrole, 3-(m-aminophenoxy)propyltrimethoxysilane, aminopropyltrihydroxysilane, 3-aminopropylmethyldiethoxysilane, 3-aminopropyldiisopropylethoxysilane, 3-aminopropyldimethylethoxysilane, or a combination thereof.

11. The solid electrolytic capacitor according to claim 8, wherein: The monoamino-functional silane is a secondary amine.

12. The solid electrolytic capacitor according to claim 11, wherein: The secondary amine is N-butylaminopropyltrimethoxysilane, N-ethylaminoisobutyltrimethoxysilane, N-methylaminopropyltrimethoxysilane, N-phenylaminopropyltrimethoxysilane, 3-(N-allylamino)propyltrimethoxysilane, cyclohexylaminomethyltriethoxysilane, N-cyclohexylaminopropyltrimethoxysilane, N-ethylaminoisobutylmethyldiethoxysilane, (phenylaminoethyl)methyl-diethoxysilane, N-phenylaminomethyltrimethoxysilane, N-methylaminopropylmethyl-dimethoxysilane, or a combination thereof.

13. The solid electrolytic capacitor according to claim 1, wherein: The organometallic compound is a diamino-functional silane having the following general formula (III): in, R1, R2 and R3 are independently alkyl, alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl or hydroxyalkyl; R4 and R5 are independently hydrogen, alkyl, independently alkenyl, aryl, heteroaryl, cycloalkyl, heterocyclyl, halogen, haloalkyl, hydroxyalkyl, or N, and Z1 and Z2 are independently organic groups.

14. The solid electrolytic capacitor according to claim 13, wherein: The diamino-functional silane is N-(2-aminoethyl)-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(6-aminohexyl)aminomethyltriethoxysilane, N-(6-aminohexyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)-11-aminoundecyltrimethoxysilane, (aminoethylaminomethyl)-phenethyltrimethoxysilane, N-3-[(amino(polypropyleneoxy)]-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrihydroxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminoisobutylmethyldimethoxysilane, (aminoethylamino)-3-isobutyldimethylmethoxysilane, or a combination thereof.

15. The solid electrolytic capacitor of claim 1 further comprising an outer polymer coating overlying the solid electrolyte and comprising conductive polymer particles.

16. The solid electrolytic capacitor according to claim 15, wherein: The outer polymer coating also includes a cross-linking agent.

17. The solid electrolytic capacitor according to claim 1, wherein: The anode body is a sintered pellet.

18. The solid electrolytic capacitor according to claim 1, wherein: The anode body is a foil.

19. The solid electrolytic capacitor of claim 1, further comprising a housing, the capacitor element being enclosed within the housing.

20. The solid electrolytic capacitor according to claim 1, wherein: The capacitor element further includes a cathode coating comprising a metal particle layer overlying the solid electrolyte, wherein the metal particle layer includes a plurality of conductive metal particles.

21. The solid electrolytic capacitor according to claim 1, wherein: The capacitor exhibited a breakdown voltage of 55 volts.

Citation Information

Patent Citations

  • Conductive adhesive agent and process for manufacturing article using the conductive adhesive agent

    US20060038304A1

  • Process for the production of electrolyte capacitors of high nominal voltage

    US20070064376A1

  • Binder removal

    US6197252B1

  • Polythiophene, water-soluble electrically conductive polymer using it, and method for producing it

    US9718905B2

  • Ta POWDER, PRODUCTION METHOD THEREFOR, AND Ta GRANULATED POWDER

    WO2014199480A1